KESALAHAN DEIKSIS DALAM KARANGAN MAHASISWA PADA NIVEAU A2 DI JURUSAN SASTRA JERMAN UM - Afifah, Lilis; Widodo, Pratomo (LingTera, 2015)
Penelitian ini bertujuan untuk mengetahui kesalahan-kesalahan yang terdapat dalam penggunaan deiksis persona, deiksis tempat, dan deiksis waktu dalam karangan mahasiswa pada Niveau A2 di Jurusan Sastra Jerman UM serta mengetahui faktor-faktor penyebabnya. Subjek penelitian adalah karangan mahasiswa yang dihasilkan dalam matakuliah Aufsatz II. Objek penelitiannya adalah kesalahan deiksis persona, kesalahan deiksis tempat, dan kesalahan deiksis waktu. Proses pengumpulan data menggunakan metode simak yang terdiri dari teknik dasar yang berwujud teknik sadap dan dilanjutkan dengan teknik simak bebas libat cakap. Instrumen penelitian adalah peneliti (human instrument). Keabsahan data dicapai melalui intrarater dan interrater. Selanjutnya data dianalisis dengan metode agih. Hasil penelitian ini adalah sebagai berikut. Dalam karangan mahasiswa ditemukan kesalahan-kesalahan yang terkandung dalam deiksis persona, deiksis tempat, dan deiksis waktu. Faktor yang menyebabkan kesalahan tersebut adalah interferensi, over generalisasi, strategi komunikasi, elemen pembelajaran bahasa asing, kurangnya kontras, kondisi sosial psikologis pembelajar, efek domino, dan redundansi. ________________________________________________________________________________________________________________ DEIXIS ERRORS IN STUDENTS’ ESSAYS IN THE DEPARTMENT OF GERMAN LITERATURE OF UM Abstract This study aimed at determining the erros in using personal deixis, spatial deixis, and temporal deixis in students’ essays on Niveau A2 in the Department of German Literature of UM and also aimed at determining the factors that motivate the occurrence of deixis errors. The subjects were essays written by students which were made in the course of Aufsatz II. The research objects were personal deixis errors, spatial deixis errors, and temporal deixis errors. The data were collected using the observation method which consisted of basic techniques in the form of recording techniques and continued by using the technique of uninvolved-conversation observation. The research instrument in this study was the researcher (human instrument). The data trustworthiness was gained through intrarater and interrater. Furthermore, the data were analyzed by using the distributional method.The results of this study are as follows. In the essay of Niveau A2 students in the German Literature Department of UM, there are some errors in using personal deixis, spatial deixis, and temporal deixis. Errors of personal deixis are realized in six forms of pronouns: personal pronouns, relative pronouns, indefinite pronouns, demonstrative pronouns, and possessive pronouns. Errors of spatial deixis are realized in adverbs and verbs. Errors of temporal deixis are realized in adverbs and tenses. The occurrences of those errors are motivated by a variety of factors, i.e. interference, over-generalization, communication strategies, elements of foreign language learning, a lack of contrast, the students’ social psychological conditions, domino effect, and redundancy. Keywords: errors, deixis, essay